2014
DOI: 10.4028/www.scientific.net/amr.1073-1076.1061
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Salt Stress on Carotenoid Pathway Genes in Watermelon

Abstract: Carotenoids, the naturally occurring isoprenoids form essential components of photosynthetic antenna and reaction centre complexes. Thus they play a significant role in absorption, dissipation and transfer of light energy for the process of photosynthesis. The expression of salt stress on carotenoid gene in watermelon leaves were studied. For that watermelon plants were subjected to different concentration of salt water. Morphological characters such as plant height, no. of fruits per plant,chlorophyll content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…No significant differences in lycopene content were reported in watermelon irrigated at different regimes, while it positively correlated with salinity increase (Ban et al, 2014). Conversely, a decrease in the expression of PSY , PDS , ZDS , LCY-β genes was reported at increasing salt concentrations (between 0 and 200 mM NaCl) by Cheng et al (2015).…”
Section: Carotenoid In Tomato and Watermelon Fruitsmentioning
confidence: 92%
“…No significant differences in lycopene content were reported in watermelon irrigated at different regimes, while it positively correlated with salinity increase (Ban et al, 2014). Conversely, a decrease in the expression of PSY , PDS , ZDS , LCY-β genes was reported at increasing salt concentrations (between 0 and 200 mM NaCl) by Cheng et al (2015).…”
Section: Carotenoid In Tomato and Watermelon Fruitsmentioning
confidence: 92%
“…They are often supplied to the plant in the form of salt; hence, a surplus may be detrimental. In fact, salt stress can decrease the expression level of genes involved in the carotenoid biosynthesis pathway, resulting in a low carotenoid content in the plant [91,92], (Table 2). Salt stress, especially a high concentration of salt (50-200 mM), has been reported to delay the growth of cowpea seedlings, reducing both the carotenoid content and net photosynthetic rate [93].…”
Section: • Plant Nutrition and Carotenoid Biosynthesismentioning
confidence: 99%
“…Such changes in the content of carotenoids in cowpea due to nutrient uptake may be the result of changes in the expression profiles of the genes involved in the biosynthesis pathway. For instance, it was reported that the treatment of the watermelon plant with salt solution significantly reduces the carotenoid content through the downregulation of the expression level of i phytoene synthase (PSY), phytoene desaturase (PDS), zeta carotene desaturase (ZDS), and lycopene beta cyclase (LCY-β) [91]. Such studies are scant in cowpea, meaning there is a need to deploy research efforts to uncover the effects of salt treatment on the genes involved in carotenoid biosynthesis and to establish the optimal nutrition system for inducing a positive change in carotenoid content in cowpea, concurrently with efforts to improve all other physiological and biological functions.…”
Section: • Plant Nutrition and Carotenoid Biosynthesismentioning
confidence: 99%